Modern Approaches To Studying Etiopathogenesis, Clinics And Treatment Of Acute Bronchiolitis In Children (Texas Journal of Medical Science, 2025)
The article describes the course , clinic, etiopathogenesis, A review of scientific articles on the diagnosis and differential diagnosis of acute bronchiolitis is presented. Acute bronchiolitis is an acute inflammatory disease of the lower respiratory tract, characterized by primary damage to the small bronchi and bronchioles, which develops mainly in children of chest age. Acute bronchiolitis most often occurs in the 1st year of life of children (in more than 80% of cases), 7-14% of them require treatment in inpatient conditions, while it is the most common cause of hospitalization in children under 2 years of age worldwide. To date, some issues of differential diagnosis remain problematic, especially the differential diagnosis of bronchiolitis and pneumonia caused by respiratory syncytial virus